Quinazolin-4-one/3-cyanopyridin-2-one Hybrids as Dual Inhibitors of EGFR and BRAFV600E: Design, Synthesis, and Antiproliferative Activity - Lamya H. Al-Wahaibi; Mohamed Hisham; Hesham A. Abou-Zied; Heba A. Hassan; Bahaa G. M. Youssif; Stefan Bräse; Alaa M. Hayallah; Mohamed Abdel-Aziz (MDPI AG, 2023)
A novel series of hybrid compounds comprising quinazolin-4-one and 3-cyanopyridin-2-one structures has been developed, with dual inhibitory actions on both EGFR and BRAFV600E. These hybrid compounds were tested in vitro against four different cancer cell lines. Compounds 8, 9, 18, and 19 inhibited cell proliferation significantly in the four cancer cells, with GI50 values ranging from 1.20 to 1.80 µM when compared to Doxorubicin (GI50 = 1.10 µM). Within this group of hybrids, compounds 18 and 19 exhibited substantial inhibition of EGFR and BRAFV600E. Molecular docking investigations provided confirmation that compounds 18 and 19 possess the capability to inhibit EGFR and BRAFV600E. Moreover, computational ADMET prediction indicated that most of the newly synthesized hybrids have low toxicity and minimal side effects.